Feasibility of local anaesthesia in lateral internal anal sphincterotomy for chronic anal fissure - Goudar, Bhimanagouda Venkanagouda; Kalburgi, Eshwar B.; Lamani, Yamanur P.; Y. C., Veerabhadra Gowd (International Surgery Journal, 2018)
Background: Fissure in Ano is one of the common and most painful anorectal conditions encountered in surgical practice. Inspite of several conservative treatment options, surgical treatment in the form of Lateral Anal Spincterotomy (LAS) remains the gold standard of treatment for Chronic Anal Fissures (CAF). Methods: Prospective comparative study conducted on 90 patients randomly divided into two groups Group A under Local anaesthesia (LA) and Group B under Spinal anaesthesia (SA) respectively. The primary outcome variables studied were postoperative pain, hospital stay, and cost effectiveness. Results: A total of 90 patients randomly divided into 45 patients in each group. There was no statistically difference in the pain at surgery, but post-operative pain was significantly less in LA group at 5th hour, 24 hours after surgery. Hospital stay in LA group is significantly less when compared to SA group (1.92, 3.75 respectively). Conclusions: LAS can be comfortably performed under LA with added advantages.